1997
DOI: 10.1292/jvms.59.479
|View full text |Cite
|
Sign up to set email alerts
|

Improved in vitro Cultivation of Babesia caballi.

Abstract: ABSTRACT. Babesia caballi infected erythrocytes were collected from the blood of an experimentally infected horse and could be continuously cultivated in vitro with parasitemia ranging from 2-4% in RPMI 1640 medium supplemented with 2 mM L-glutamine, 20 mM HEPES and 40% adult horse serum in a low oxygen atmosphere (2% O 2 , 5% CO 2 and 93% N 2 ). All attempts to increase parasitemia failed using other culture media, serum concentrations and culture vessels. However, parasite growth was enhanced by transfer of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 8 publications
1
45
1
Order By: Relevance
“…2 % and 84 . 5 % for T. equi and B. caballi, respectively, were observed (Avarzed et al 1997). In contrast to the present study, these authors found a significant decrease in prevalence in animals between 11 and 16 years, which may be due to the large stratification intervals (1, 2, 3, 4, 5 years, 6-10 years, 11-16 years) and the small sample size in this particular stratum (n=5).…”
Section: Discussioncontrasting
confidence: 99%
“…2 % and 84 . 5 % for T. equi and B. caballi, respectively, were observed (Avarzed et al 1997). In contrast to the present study, these authors found a significant decrease in prevalence in animals between 11 and 16 years, which may be due to the large stratification intervals (1, 2, 3, 4, 5 years, 6-10 years, 11-16 years) and the small sample size in this particular stratum (n=5).…”
Section: Discussioncontrasting
confidence: 99%
“…Several reports on the prevalence of equine babesiosis in Mongolia, which shares a border with the Xinjiang, have been published [1,3,14]. These studies demonstrated that both B. equi and B. caballi infections in horses are widespread in Mongolia.…”
mentioning
confidence: 98%
“…In the both ELISAs, the secondary goat anti-donkey IgG antibody (Rockland Immunochemicals, 1:4,000) was used. The IFAT using B. equi parasite or B. caballi parasite as antigens was performed as described previously [1], except that the secondary rabbit anti-donkey IgG antibody (Bethyl Laboratories, 1:400) was used.…”
mentioning
confidence: 99%
“…Chronically infected horses represent a reservoir infecting ticks, which subsequently transmit the parasites to other equids. Piroplasms can be detected directly by microscopical examination of Giemsa-stained thin blood smears or by polymerase chain reaction (PCR) (Bruning, 1996), and for indirect diagnosis, the immunofluorescence antibody test (IFAT) is the most widely used technique (Gummow et al 1996 ;Avarzed et al 1997 ;Heuchert et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Chronically infected horses represent a reservoir infecting ticks, which subsequently transmit the parasites to other equids. Piroplasms can be detected directly by microscopical examination of Giemsa-stained thin blood smears or by polymerase chain reaction (PCR) (Bruning, 1996), and for indirect diagnosis, the immunofluorescence antibody test (IFAT) is the most widely used technique (Gummow et al 1996 ;Avarzed et al 1997 ;Heuchert et al 1999).The epidemiology of equine piroplasmoses has been investigated in various studies (Mahoney, 1969 ;Mahoney and Ross, 1972 ;Ross and Mahoney, 1974 ;Smith, 1983 ;Dallwitz et al 1987 ;Medley et al 1993). In 2004, a study was conducted in a domestic horse population in south-western Mongolia (Rü egg et al 2007).…”
mentioning
confidence: 99%